NAHDLATUL ULAMAS CONCEPT OF PROMOTING GLOBAL HARMONY THROUGH RELIGION TWENTY - Hannase, Mulawarman; Hamzah, Idil; Akbar, Akbar; Zahran, Mostafa (Al-Qalam, 2024)
This article explores the concept of Nahdatul Ulama in promoting global harmony through the R 20 activities. The research employs a qualitative method with data sourced from library research. The article concludes that R 20 has taken concrete steps, facilitated by Nahdatul Ulama, to foster global harmony. These efforts culminated in a collective agreement termed the Communique focusing on four key aspects elucidating religion as a conflict resolution: firstly, tolerance (Tasamuh), in the dynamics of social diversity, emphasizing the development of tolerant attitudes among religious communities as an expression of the ability to bear the burden of differing perspectives. Secondly, ecotheology, a theological concept exploring the interconnectedness of religion and nature, encourages integrating spiritual dimensions with environmental responsibilities. Thirdly, Interfaith Dialogue underscores the necessity for in-depth dialogues to achieve peace among nations and religions. With openness, communication, and compassion, conflicts are viewed as opportunities to enhance understanding, fostering harmonious relationships among religious practitioners. Lastly, the article highlights the active roles of government and religious leaders in addressing extremism and intolerance, contributing to the realization of harmony. The concept used by NU as a basis for compiling the 'Communique' is special because it specifies universal religious values and strengthens the national program, namely Religious Moderation. This is based on NU's commitment as a religious organization that maintains traditionalist theological values as well as being a guardian of national policy.